2017
DOI: 10.4073/csr.2017.16
|View full text |Cite
|
Sign up to set email alerts
|

Vocational and business training to improve women's labour market outcomes in low‐ and middle‐income countries: a systematic review

Abstract: This Campbell systematic review examines the impact of vocational and business training targeted at women in low‐ and middle‐income countries. The review summarises evidence from thirty‐five quantitative studies with an experimental or quasi‐experimental design. The review summarises the impact of 30 interventions, containing data from over 80,000 women. The qualitative narrative meta‐synthesis includes findings from 50 studies. Included studies are experimental and quasi‐experimental evaluations which measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
14

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 125 publications
0
33
0
14
Order By: Relevance
“…The study findings were inconsistent with a study carried out by Raven and Vu Le (2015) which showed that business training could improve microenterprise performance and has a number of other positive results, such as increasing motivation, success, and perceptions of entrepreneurs. According to Chinen et al (2018) study established that by empowering women and promoting the rule of law in their communities ensure that everyone truly is equal before the law and equally protected by the law.…”
Section: Discussionmentioning
confidence: 99%
“…The study findings were inconsistent with a study carried out by Raven and Vu Le (2015) which showed that business training could improve microenterprise performance and has a number of other positive results, such as increasing motivation, success, and perceptions of entrepreneurs. According to Chinen et al (2018) study established that by empowering women and promoting the rule of law in their communities ensure that everyone truly is equal before the law and equally protected by the law.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors considered the role of contextual factors (e.g., time constraints, distance, cost of transport, economic and labour market conditions) (Chinen et al, 2017).…”
Section: Social Insurancementioning
confidence: 99%
“…Moreover, the authors caution that study quality was a significant moderator, with higher effect sizes found on lower quality studies, implying that even the very small average effects observed may represent an over-estimate. Similarly, Chinen et al (2017) conducted a meta-analysis of 16 randomisedcontrol-trial (RCT) studies assessing the effectiveness of vocational training interventions on adult women's employment prospects in lowand middle-income countries. The authors found a significant but rather small positive effect (participants were 11% more likely than controls to secure work) alongside non-significant indications that the positive effects of trainings on employment fell when looking at horizons beyond six months post-training.…”
Section: What Is the State Of Vocational Training Systems In Middle-income Countries?mentioning
confidence: 99%